Changing Remittance Patterns in Nepal: Evidence from the Nepal Living Standards Survey (NLSS) III and IV - Acharya, Bala Ram (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This study analyzes remittance patterns between the third Nepal Living Standards Survey (NLSS) in 2010/2011 and the fourth in 2022/2023. This analysis examines ten years of remittance-receiving and utilization trends in relation to household livelihoods, social transformation, trust in financial institutions, and policy implications. It examines current sources, transfer methods, and household uses of remittances from national data. Analysis shows that remittances are essential to household income and livelihood. The remittance data show a significant contribution to economic and social resources. It shows that families are employing various strategies to manage risks to their livelihoods in the current context. As illustrated in NLSS-2022-23, formal banking systems have replaced the traditional cash exchange system. Daily expenses of remittance-receiving families continue to provide substantial support for family needs. Rising loan repayments among migrants’ households have significantly reduced their capability to save remittances. It indicates the possibility of debt dependency at the family level. However, remittances promote social mobility and contribute to economic transformation at the local level. This study concludes that effective policy interventions are essential to achieve social empowerment through remittance. The government also needs to provide migrants with the skills and knowledge necessary for entry into the workforce through appropriate policy initiatives. Local government policies may promote profitable investment that supports migrants’ sustainable lives.